Levetiracetam Affects Differentially Presynaptic Proteins in Rat Cerebral Cortex - Marcotulli, Daniele; Fattorini, Giorgia; Bragina, Luca; Perugini, Jessica; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2017)
Presynaptic proteins are potential therapeutic targets for epilepsy and other neurological diseases. We tested the hypothesis that chronic treatment with the SV2A ligand levetiracetam affects the expression of other presynaptic proteins. Results showed that in rat neocortex no significant difference was detected in SV2A protein levels in levetiracetam treated animals compared to controls, whereas levetiracetam post-transcriptionally decreased several vesicular proteins and increased LRRK2, but not their mRNA levels. Analysis of SV2A interactome indicates that the presynaptic proteins regulation induced by levetiracetam reported here is mediated by this interactome, and suggests that LRRK2 plays a role in forging the pattern of effects.